Azithromycin-Related Bicytopenia: An Exceptional Adverse Effect - Fatma Hammami; Salma Fourati; Makram Koubaa; Fatma Smaoui; Khaoula Rekik; Chakib Marrakchi; Mounir Ben Jemaa (Journal of Pharmaceutical Care, 2020)
Macrolide antibiotics are commonly prescribed and are usually well tolerated. Azithromycin-related anemia and thrombocytopenia has not been reported previously. Here, we present the case of a 63-year-old man with bicytopenia following azithromycin treatment for ocular toxoplasmosis. He developed both thrombocytopenia and anemia after less than 7 days of treatment. Pyrimethamine, known for its hematologic side effects, was stopped on admission. However, the platelets drop continued to worsen. Then, azithromycin has been incriminated. All his symptoms and laboratory abnormalities were recovered within 7 days after the discontinuation of azithromycin treatment. Physicians must be aware of azithromycin-induced bicytopenia because its early detection can decrease the severity of these side effects.